Padrões ecomorfológicos de assembleias de peixes em córregos da bacia do rio Pirapó, região norte do Paraná, Brasil. - Pagotto, João Paulo Alves (2014)
In water bodies located in areas under anthropogenic impacts, the structural patters of fish assemblages can show peculiar characteristics according to the local environmental conditions. In this sense, it is needed to answer some questions about the consequences of human interference on these ecosystems, especially those questions related to the effects of urban and rural conditions on ecomorphological diversity and ecological structure of stream fish assemblages. The study was conducted in second and third order streams from the Pirapó River Basin, located close to the cities of Maringá and Astorga, Paraná state, Brazil, where it was selected nine samples sites along a rural and urban gradient. Different types of statistical methods were performed to test the hypotheses of this document. The results showed the influence of urban and rural conditions on ecomorphological structure of the ichthyofauna, revealing some adaptive answers. Therefore, this study presented the importance of the ecomorphological approach as a tool to provide information about adaptive patterns originated from changes in environmental conditions. Furthermore it confirms the need for actions to recover the riparian vegetation in hydrographic basins from small order streams.